Accursius, Bartolo and Baldus and the impact of their teaching in private law at the instance of the Lex Aquilia - Claudia Lydorf (Journal on European History of Law, 2011)
Modern legal scholars are increasingly encountering ancient European legal institutions, which may be considered "extinct" in Europe but continue to exist in similar forms in non-European legal systems and, through globalization, are making their way back to Europe. This presents the challenge of reconciling legal positions derived from various laws. Against this backdrop, it is worth remembering that the development of international private law and the harmonization of European civil law have a long tradition. As early as the 12th century, the revival of Justinian's Corpus Iuris Civilis in Bologna successfully provided a unified legal framework for civil law that was recognized across Europe. This article presents the personal, institutional, and methodological origins of European legal science. Additionally, the Lex Aquilia is used as an example to demonstrate certain legal concepts developed during this early period, whose influence can still be observed in modern times.